The widely distributed hard tick, Haemaphysalis longicornis, can retain canine parvovirus, but not be infected in laboratory condition - MORI, Hiroyuki; TANAKA, Tetsuya; MOCHIZUKI, Masami (Journal of Veterinary Medical Science, 2015)
Ticks are known to transmit various pathogens, radically threatening humans and animals. Despite the close contact between ticks and viruses, our understanding on their interaction and biology is still lacking. The aim of this study was to experimentally assess the interaction between canine parvovirus (CPV) and a widely distributed hard tick, Haemaphysalis longicornis, in laboratory condition. After inoculation of CPV into the hemocoel of the ticks, polymerase chain reaction assay revealed that CPV persisted in inoculated unfed adult female ticks for 28 days. Canine parvovirus was recovered from the inoculated ticks using a cell culture, indicating that the virus retained intact in the ticks after inoculation, but significant positive reaction indicating virus infection was not detected in the tick organs by immunofluorescence antibody test using a monoclonal antibody. In the case of ticks inoculated with feline leukemia virus, the virus had shorter persistence in the ticks compared to CPV. These findings provide significant important information on the characteristic interaction of tick with non-tick-borne virus.